TINJAUAN YURIDIS TERHADAP PERBUATAN MENIMBUN MASKER DI AWAL PANDEMI COVID-19 : (Ditinjau Dari Undang - Undang No.7 Tahun 2014 Tentang Perdagangan) - Hanafi Widya Al Fahd, (2021)
Medical equipment in the form of masks have been indispensable since the outbreak of the Covid-19 pandemic in early 2020. This paper discusses the issue of legal certainty and protection for business actors and the public as consumers in relation to law enforcement against mask hoarders during the Covid-19 virus outbreak in terms of Law Number 7 of 2014 concerning Trade that's using a juridical normative approach. The essence of the application of legal certainty must be realized in advance so that the concept of legal protection for consumers through enforcement is interpreted properly. So that law enforcement can be realized based on the principle of legal certainty, the principle of benefit and the principle of justice. These three concepts must be sustainable in supporting the operation of the principle of legal protection.